1989
DOI: 10.1152/jappl.1989.66.4.1699
|View full text |Cite
|
Sign up to set email alerts
|

Postural changes in spontaneous and evoked regional diaphragmatic activity in dogs

Abstract: We addressed the question whether gravity-dependent differences in passive tension and length of the diaphragm are associated with differences in its regional activation. By using intramuscular electrodes, we measured the electromyographic activity of different parts of the diaphragm (Edi) during quiet breathing in several postures in 13 anesthetized mongrel dogs. The Edi of the left and right costal hemi-diaphragm was compared between the left and right lateral decubitus postures, whereas that from the subste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…A frequently recurring criticism of the measurement of EAdi with esophageal or implanted electrodes during spontaneous breathing is that the signal strength is affected by changes in muscle length or lung volume. This critique is based on studies of evoked diaphragm compound muscle action potentials (15) or outdated methodology that does not control for interelectrode distance (16). Using appropriate methodology, EAdi obtained during spontaneous breathing is not artifactually influenced by changes in muscle length, chest wall configuration, or lung volume (17,18).…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…A frequently recurring criticism of the measurement of EAdi with esophageal or implanted electrodes during spontaneous breathing is that the signal strength is affected by changes in muscle length or lung volume. This critique is based on studies of evoked diaphragm compound muscle action potentials (15) or outdated methodology that does not control for interelectrode distance (16). Using appropriate methodology, EAdi obtained during spontaneous breathing is not artifactually influenced by changes in muscle length, chest wall configuration, or lung volume (17,18).…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…The diaphragm in our animals, however, was not paralyzed. No attempt was made to record diaphragmatic EMG activity in the present study, because this activity, when recorded with intramuscular electrodes, is well known to show artifactual changes with alterations in the conductivity of the environment surrounding the electrodes (7) or in the length of the muscle fibers (19,22). However, similar to neural drive to the parasternal intercostals (10,11), neural drive to the diaphragm is primarily governed by supraspinal control mechanisms, and measurements of motoneuron synchronization in cats by Vaughan and Kirkwood (34) showed that phrenic motoneurons and parasternal intercostal motoneurons receive common monosynaptic inputs.…”
mentioning
confidence: 99%
“…The asymmetrical non-respiratory activity in the left and right diaphragm was considered to be due to the changes in electrical environment [14]. However, it could not be the case in the present experiment, because the diaphragm in cats is smaller than that in dogs and small displacements by contraction may cause the relatively stable electrical recording environment.…”
Section: Activities During Free Movementmentioning
confidence: 71%